Search Unemployment with Advance Notice - Garibaldi, Pietro (IMF Working Papers; Working Paper, 1998)
This paper proposes and solves a search model in which job separation requires mandatory notice. When jobs are subject to idiosyncratic uncertainty, firms would issue advance notice even with good business conditions. We show that such precautionary policy is not pursued if it entails sufficiently high productivity losses. If workers can search on the job, an increase in advance notice increases job to job movements, reduces unemployment flows, and has ambiguous effects on unemployment. Results are consistent with the fact that North American and European labor markets, despite their differences in job security provisions, experience similar turnover rates and dissimilar unemployment flows.